2014
DOI: 10.1371/journal.pone.0103983
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the NucliSens EasyQ v2.0 Assay in Comparison with the Roche Amplicor v1.5 and the Roche CAP/CTM HIV-1 Test v2.0 in Quantification of C-Clade HIV-1 in Plasma

Abstract: Human immunodeficiency virus type 1 (HIV-1) genetic diversity poses a challenge to reliable viral load monitoring. Discrepancies between different testing platforms have been observed, especially for non-clade-B virus. Therefore we compare, in antiretroviral therapy (ART)-naïve South African subjects predominantly infected with HIV-1 clade-C, three commercially available assays: the COBAS AmpliPrep/COBAS TaqMan HIV-1 Test version 2.0 by Roche (CAP/CTM v2.0), the BioMérieux NucliSens Version 2.0 Easy Q/Easy Mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…Moreover, group 1 is prone to inherent precision issues, especially since the limits of quantification for the four assays are different. In the group of samples with viral loads of Ͼ3.00 log copies/ml (group 4), which includes either virological failures or untreated cases, the NucliSens v2.0 assay was less sensitive and tended to underestimate viral loads, as reported by others (23). Taken together, the data suggest that the NucliSens v2.0 assay has lower viral load readings and inferior precision and accuracy.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Moreover, group 1 is prone to inherent precision issues, especially since the limits of quantification for the four assays are different. In the group of samples with viral loads of Ͼ3.00 log copies/ml (group 4), which includes either virological failures or untreated cases, the NucliSens v2.0 assay was less sensitive and tended to underestimate viral loads, as reported by others (23). Taken together, the data suggest that the NucliSens v2.0 assay has lower viral load readings and inferior precision and accuracy.…”
Section: Discussionsupporting
confidence: 50%
“…Our data indicate that the four assays could successfully quantify the main subtypes, albeit with different degrees of efficiency. Discrepancies between different testing platforms (including the NucliSens v2.0 assay) have been predominantly reported for HIV-1 clade C samples, especially in the low-viremic range (23). In a different study that compared the NucliSens v2.0 assay and six other assays, including the RealTime assay, large quantitative differences, which exceeded 0.5 log IU/ml for approximately 50% of the tested samples, were identified for subtype AE and BC samples, although very similar mean viral load values were observed across the assays for subtype B samples (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, higher variations were observed at low viral loads, ie; at 200 copies/ml (%CV 3.34, 1.97) respectively which was found to be less than the Abbott assay. Thus, variation observed at low viral load results agrees with previously reported study by Swenson et al, in 2014 where comparisons were based on 4221 paired samples [37], These variations could be attributed to the discrepancies in different testing platforms in quantifying subtype C samples as reported earlier [38]. Apart from variations observed while using such platforms, the parameters like type of sample and its integrity were assessed in one of the study wherein good precision as well as accuracy was reported for another POC (Liat HIV Quant (IQuum) platform) in comparison with other platforms (Roche CAP/CTMv2 and Abbott RealTime HIV-1) [39].…”
Section: Discussionsupporting
confidence: 90%
“…Diagnostic accuracy studies are relatively simple, and many laboratories in sub-Saharan Africa perform in-house and/or community based evaluations of new assays, but few publish the results [ 24 , 25 ]. Diagnostic accuracy studies are good introductions to laboratory and clinical research.…”
Section: Discussionmentioning
confidence: 99%